Tunable Polymeric Scaffolds for Enzyme Immobilization - Rodriguez-Abetxuko, Andoni; Sánchez-deAlcázar, Daniel; Muñumer, Pablo; Beloqui, Ana (Frontiers in Bioengineering and Biotechnology, 2020)
The number of methodologies for the immobilization of enzymes using polymeric supports is continuously growing due to the developments in the fields of biotechnology, polymer chemistry, and nanotechnology in the last years. Despite being excellent catalysts, enzymes are very sensitive molecules and can undergo denaturation beyond their natural environment. For overcoming this issue, polymer chemistry offers a wealth of opportunities for the successful combination of enzymes with versatile natural or synthetic polymers. The fabrication of functional, stable, and robust hybrid materials (catalytic nanoparticles, capsules, hydrogels, or films) has been proven advantageous for several applications such as biomedicine, organic synthesis, biosensing, and bioremediation. In this review, supported with recent enzyme-polymer hybrid examples from the literature, we provide an overview of the methods used to combine both macromolecules, as well as the future directions and the main challenges that are currently being tackled in this field.